UPAYA MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS 3 SD NEGERI POLOKARTO 01 MELALUI PENERAPAN PAPAN SKOR BERBASIS GAMIFIKASI ALA MOBILE LEGENDS - Siti Yulaika; MS Khabibur Rahman; Painem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the results of increasing the learning motivation of SD Negeri Polokarto 01 students after being given actions in the form of a gamification-based scoreboard method or strategy in the style of Mobile Legends and using Classroom Action Research, which was carried out twice. The subjects in this study are 3rd-grade students of SD Negeri Polokarto 01, totaling 20 students. The results of the research percentage in the first cycle of questionnaire answers were only 23% of students with high learning motivation and 20% with sufficient learning motivation. Meanwhile, it is known that 30% of students have less motivation to learn, and 27% of students do not have the motivation to learn. The observation results showed that students' interest in learning was still low, not disciplined, and the classroom atmosphere was noisy outside the learning context. The cycle continued in phase II and obtained results of 59% of students with high learning motivation and 27% with sufficient learning motivation. Meanwhile, it is known that 8% of students have less motivation to learn, and 6% of students are not motivated in learning. Observations show that students' interest in learning increases, discipline increases, and in-person learning is conducive.